2017
DOI: 10.1200/jco.2017.35.15_suppl.10009
|View full text |Cite
|
Sign up to set email alerts
|

FDA analysis of enrollment of older adults in clinical trials for cancer drug registration: A 10-year experience by the U.S. Food and Drug Administration.

Abstract: 10009 Background: Older adults are a growing segment of our oncology population, with an expected increase in cancer incidence of 67% from 2010 to 2030 in people age 65 and older. However, older adults have been proportionally underrepresented in clinical trials. We sought to analyze the age-related enrollment of cancer patients onto trials supporting registration of new drugs or new indications approved by the US Food and Drug Administration from 2005 to 2015. Methods: This study involved retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 0 publications
4
96
0
1
Order By: Relevance
“…We found a difference between over 80s and under 80s. This finding agrees with a recent U.S. Food and Drug Administration analysis of the enrollment of older adults in clinical trials for cancer drug registration . Javid et al did not find any difference in invitation rates between older (over 65) and younger (under 65) patients—in contrast to a case‐control study based on 10 Cancer and Leukemia Group institutions .…”
Section: Discussionsupporting
confidence: 86%
“…We found a difference between over 80s and under 80s. This finding agrees with a recent U.S. Food and Drug Administration analysis of the enrollment of older adults in clinical trials for cancer drug registration . Javid et al did not find any difference in invitation rates between older (over 65) and younger (under 65) patients—in contrast to a case‐control study based on 10 Cancer and Leukemia Group institutions .…”
Section: Discussionsupporting
confidence: 86%
“…Results of these studies may not represent the current profile of distress in HL, however, as treatment approaches evolved [ 7 12 ] and recommendations for managing late effects in HL survivors [ 2 ] emerged during the 15 years since these studies were published. In addition, clinical trial participants differ from patients receiving treatment in a non-experimental setting [ 13 ]. More recent studies estimating the prevalence of distress in hematologic malignancies have not distinguished between leukemias and lymphomas [ 14 ], have not described distress separately in HL and non-Hodgkin lymphoma [ 15 , 16 ] or have evaluated distress in HL patients receiving a bone marrow transplant [ 17 ], which represents a minority of HL cases.…”
Section: Purposementioning
confidence: 99%
“…A recent US Food and Drug Administration analysis of trials supporting registration of new cancer therapies and conducted from 2005 to 2015 found that older people, in particular, those aged >75 years, were under-represented 31. Earlier, Lewis and colleagues5 found that only 32% of phase II and III cancer trials enrolled older patients, despite the fact that 61% of patients with incident cancers were older.…”
Section: Discussionmentioning
confidence: 99%